Histopathological study of soft-tissue tumors in a medical college in South India: A two-year study - Jyoti Brahmaiah; Bharathi Sree; Sai Prasad BV; Sai Sailesh Kumar Goothy (Asian Journal of Medical Sciences, 2023)
Background: Soft tissue can be defined as non-epithelial extraskeletal tissue of the body exclusive of the reticuloendothelial system, glia, and supporting tissues of different parenchymal organs. These tumors are a highly heterogeneous group and are classified into benign, intermediate, and malignant forms according to the adult tissue they resemble. They can occur in all sites of the body. Aims and Objectives: The present study was undertaken to assess the histopathological pattern of various soft-tissue tumors. Materials and Methods: This is a prospective observational study for a period of 2 years, in which 152 soft-tissue tumors were analyzed and classified primarily as per the WHO classification. The age-wise, sex-wise, and site-wise distribution and the histopathological spectrum of soft-tissue tumors were studied. Results: A total of 152 soft-tissue tumors were included in the study, of which 90.79% were benign tumors, 5.92% were malignant, 2.63% were intermediate grade tumors, and 0.66% was of uncertain malignant potential. Maximum number of patients belonged to the 41–50-year age group. Males constitute 53.29% cases and females, 46.71% with a male-to-female ratio of 1.14:1. Lipoma was the most common soft-tissue tumor in the present study. Conclusion: Overall soft-tissue tumors are a rare category of tumors with benign tumors vastly outnumbering malignant tumors. The diagnosis of soft-tissue tumors needs a meticulous approach and team effort. Proper examination of the gross specimen and careful sampling of the tumor is required for the correct diagnosis. Hematoxylin- and Eosin-stained sections remain very important for the diagnosis of soft-tissue tumors along with immunohistochemistry and molecular markers.